HTR-8/SVneo: A model for epithelial to mesenchymal transition in the human placenta. (15th January 2020) - Msheik, Hiba; Azar, Joseph; El Sabeh, Malak; Abou-Kheir, Wassim; Daoud, Georges
Abstract: Introduction: The placenta is a transitory organ essential for proper fetal maturation and growth. Trophoblasts, the main cell type of the placenta, differentiate along the villous or extravillous pathways. The ability of villous cytotrophoblasts to undergo an epithelial-to-mesenchymal transition to form the invasive extravillous trophoblasts is vital for a successful pregnancy outcome. Many trophoblastic cell lines, including HTR-8/SVneo, have been widely used to investigate extravillous trophoblast biology and functions. We have previously reported that HTR-8/SVneo cell line contains a mixed populations of epithelial and mesenchymal cells. Uncovering the mechanisms underlying this heterogeneity is essential for the proper study of normal and pathological placental function. Methods: HTR-8/SVneo was subjected to monoclonal isolation, spheroid formation assay and cell sorting to isolate pure epithelial and mesenchymal populations. These fractions were maintained in culture and assessed for expression of epithelial and mesenchymal markers using quantitative real-time PCR and immunofluorescence. In addition, the implication of TGFβ in the EMT process was investigated using a selective inhibitor of TGF-βR1 (A83-01). Results: Passaging of the pure epithelial population maintained under normal culture condition resulted in a shift to a mesenchymal phenotype. This transition was reduced upon inhibiting TGF-βR1. Similarly, E-cadherin positive HTR-8/SVneo spheroids plated in 2D culture resulted in the emergence of streams of invading mesenchymal cells. Discussion: HTR-8/SVneo cell line is undergoing EMT under normal culture condition and TGFβ is a key mediator of this process. Our results raise the possibility of using HTR-8/SVneo cell line as a model to investigate EMT in extravillous trophoblast cells. Highlights: HTR-8/SVneo cell line contains epithelial and mesenchymal cells. HTR-8/Svneo are undergoing an EMT phenomena. FACS sorted E-cadherin cells show the occurrence of EMT. TGF-beta regulate the process of EMT in HTR-8/SVneo.